THE IMPACT OF COVID-19 TOWARDS EMPLOYEE MOTIVATION AND DEMOTIVATION INFLUENCE EMPLOYEE PERFORMANCE: A STUDY OF SAYURMOMS - Clara Anisah; Anggara Wisesa (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Indonesia as a developing country, development is happening very rapidly and competing with each other in prioritizing quality. To maximize quality, good human resource management is needed. In their growing stage, there is a small business that is still developing called ‘Sayurmoms’. From the 10 months Objective Key Result (OKR) From July 2020 to May 2021. Sayurmoms only reach average at level 31,5% during COVID-19. The research objective in this research is to understand the employee motivation and demotivation during COVID-19 that influenced the employee performance on Sayurmoms. The research methodology approach will be qualitative research, which is a way for examining and comprehending an individual's or an organization's impact on a social or human issue. In this case the individuals are the employees in Sayurmoms and the human problem is the motivation and demotivation during COVID-19. This study will employ qualitative phenomenology analysis in order for the researcher to gain a better understanding of the phenomenon from Sayurmoms’ employee’s point of view regarding the COVID-19 phenomenon that causes the employee to work from home and its impact on their motivation and demotivation with using in-depth interview for the data collection. This research plays a role in giving the solution for Sayurmoms in mitigating the employee demotivation and increasing employee motivation. Keywords: COVID-19 Pandemic; Employee Motivation; Employee Demotivation; Employee Performance